PENGEMBANGAN KONTEN INSTAGRAM ECODEEN: PELATIHAN HYBRID UNTUK MENINGKATKAN KEBERLANJUTAN KOMUNITAS - Kharishma, Vidya; Nurrul Haq, Bayyinah; Wahyuti , Tri (Jurnal Abdimas Bina Bangsa, 2025)
Communities have an important role in campaigning for sustainable development programs or Sustainable Development Goals (SDGs).  One of them, EcoDeen is a Muslim community that focuses on increasing environmental awareness.  Instagram is currently the primary media outlet for the EcoDeen Community campaign, and its content is updated every week.  However, EcoDeen's Instagram social media has a lower level of engagement from likes, comments, shares, saves, and reposts than similar communities.  Therefore, this community service aims to increase brand awareness of the Ecoden Community by providing training on how to develop EcoDeen Instagram content.  The hope is that with increased engagement, the EcoDeen Community campaign will be able to reach a larger audience.  The method used in this community service is the waterfall method, with stages of preparation, training, mentoring, and evaluation carried out sequentially and systematically.  Following training and mentoring, the Ecodeen Community discussed creating a new campaign strategy and improving the quality of its Instagram media content.  The next steps for sustainability of the Ecodeen Community mentoring program include coaching on infographic content creation, training on Instagram analytics tools, and preparing Ecodeen's branding strategy.